Response of Leek (Allium Porrum L.) to Different Irrigation Water Levels Under Rain Shelter - Kiremit, Mehmet Sait; Arslan, H. (Taylor and Francis Inc. 325 Chestnut St, Suite 800 Philadelphia PA 19106, 2018)
A pot experiment was conducted to investigate the effects of different water levels on water-use efficiency, yield and growth parameters of leek (Allium porrum L.) and was carried out in the practical research field of Ondokuz Mayıs University in Turkey. Different irrigation water levels were based on the weight changes of each pot and included 5 irrigation treatments [25% (I25), 50% (I50), 75% (I75), 100% (I100) and 118% (I118) times of consumed water]. Decreases in irrigation water resulted in decreases in plant height, stem diameter, leaf and stem fresh weights, leaf and stem dry weights and leaf area, but did not significantly affect leaf number or chlorophyll content. A yield-response factor of 1.26 was obtained, implying that the leek crop was sensitive to water stress caused by deficit irrigation. Comprehensive analysis of yield, water use efficiency, and evapotranspiration, the I75 treatment can be suggested for leek production in water-scarce regions. © 2018 Taylor & Francis.
Keywords: Deficit Irrigation; Irrigation Rates; Water Consumption; Water Stress; Yield Response Factor